Transforming bicycle market: Assessing cyclists route preferences on different bike types in a choice experiment - Michael Hardinghaus; Jan Weschke (Transportation Research Interdisciplinary Perspectives, 2023)
Cycling is an environmentally friendly and healthy mode of transport that can be supported by appropriate road infrastructure. Most recently, the bike market is being differentiated and sales of innovative bike types such as cargo bikes and e-bikes are growing rapidly. Even though the importance of these particular vehicles is increasing greatly, little is known about specific route preferences applicable. Hence, we evaluate a graphically assisted online discrete choice experiment. We investigate the route preferences of users of different types of bikes. By applying mixed logit models, we estimate the differences in the valuation of infrastructure characteristics between users of regular bikes, cargo bikes and e-bikes. Results show that users of both, cargo bikes and e-bikes value a high-quality infrastructure even higher than users of regular bikes do. Higher route requirements of users of innovative bike types strengthen the importance of upgrading the infrastructure as these vehicles are becoming increasingly popular.